Step-By-Step Instructions for Retina Recordings with Perforated Multi Electrode Arrays - Reinhard, Katja (Public Library of Science, 2014)
Multi-electrode arrays are a state-of-the-art tool in electrophysiology, also in retina research. The output cells of the retina, the retinal ganglion cells, form a monolayer in many species and are well accessible due to their proximity to the inner retinal surface. This structure has allowed the use of multi-electrode arrays for high-throughput, parallel recordings of retinal responses to presented visual stimuli, and has led to significant new insights into retinal organization and function. However, using conventional arrays where electrodes are embedded into a glass or ceramic plate can be associated with three main problems: (1) low signal-to-noise ratio due to poor contact between electrodes and tissue, especially in the case of strongly curved retinas from small animals, e.g. rodents; (2) insufficient oxygen and nutrient supply to cells located on the bottom of the recording chamber; and (3) displacement of the tissue during recordings. Perforated multi-electrode arrays (pMEAs) have been found to alleviate all three issues in brain slice recordings. Over the last years, we have been using such perforated arrays to study light evoked activity in the retinas of various species including mouse, pig, and human. In this article, we provide detailed step-by-step instructions for the use of perforated MEAs to record visual responses from the retina, including spike recordings from retinal ganglion cells and in vitro electroretinograms (ERG). In addition, we provide in-depth technical and methodological troubleshooting information, and show example recordings of good quality as well as examples for the various problems which might be encountered. While our description is based on the specific equipment we use in our own lab, it may also prove useful when establishing retinal MEA recordings with other equipment.